Guimarães Rosa e Martin Heidegger: duas visões sobre o Nazismo - SILVA, Leonardo Castro da (Universidade Federal do Pará, 2014)
In 1970 occurred the publication of the posthumous book Ave, palavra of Guimarães Rosa (1908-1967) which gathers some texts of the author, from this collection of texts it has chosen the chronicles “O mau humor de Wotan”, “A velha” and “A senhora dos segredos”, which revolve around the context of German Nazism and expose a contrary position to National Socialism. At first moment, this work aims to show how Benedito Nunes (1929-2011) was guided by an interpretive tendency designed by heideggerianos commentators before the complete works [Gesamtausgabe] (2001), such a tendency postulates that there is not, in the philosophy of Martin Heidegger (1889-1976), a link between the political thought and the philosophical. The next step exposes the heideggerian notion in Ser e Verdade (2001) in which the german philosopher proposes an ideological basis for Nazism, being in favor of this with certain restrictions. This way, it shows how the complete works set out arguments that point to a limitation in relation to the commentators who produced before its publication about Politics and Philosophy in Heidegger. In subchapter about O local da diferença (2005), it deals with trauma and testimony as central concepts that the author puts to theorize the Literatures of the 20th century in the contexts of war and authoritarian regimes. After, it makes a critical reading based on the premise of philosophical political thought on Heidegger in the chronicles of Rosa, because they expose images from the period of Nazi Germany when the brazilian writer was working as a diplomat. The second review of the war chronicles will be made based on the concepts of trauma and testimony formulated by Seligmann-Silva (1964), because the works of Rosa treated demonstrate the level of authoritarianism of the Nazi party. Finally, it will be made a definition of the concept of reception of Hans Robert Jauss (1921-1997) to then discuss the authors who made the critical reception of the chronicles of Guimarães Rosa.